Study in the Clinical Outcomes and Quality of Life in Epilepsy Patients at Bangkok Hospital Headquarters - Yongprawat, Thitaree; Jarrat, RN, Laksamee; Seeboonruang, MSc, Akanitha; Chansakul, MD, Chakorn; Danchaivijitr, MD, Chotipat (The Bangkok Medical Journal, 2020)
OBJECTIVES: To evaluate clinical outcomes of care for patients with epilepsy (PWEs) and assess the quality of life (QOL) for PWEs in Epilepsy Clinic at Bangkok Hospital Headquarters (BHQ). MATERIALS AND METHODS: A cross-sectional descriptive study was conducted at the Epilepsy Clinic in a tertiary care private hospital. The study population included patients with epilepsy who are over 18 years of age. It took place from July 2016 to December 2018. The clinical outcomes were assessed by the frequency of seizures and QOL. The QOL was assessed by the Thai version of QOLIE-31-P questionnaire. It comprises 38 questions about patients’ health and the daily activities of patients with epilepsy. The Epilepsy Clinic’s compliance with the Epilepsy Quality Measurement set (EQMs) standard was used to evaluate the patient’s care process. Descriptive statistics were used in this study to determine compliance with quality measurements. A Fisher’s Exact Test was used to compare the seizure frequency between baseline and 12-week follow-up and a Paired t-test statistic was used to compare QOL scores among baseline and 12-week follow-up. RESULTS: A total of 66 participants were used in our survey study. 46 (69.7%) of them were female. The mean age was 35.18±12.52 years. The average age of the first seizure onset was 27.21±13.75 years. 49 (74.2%) had a duration of epilepsy of more than 5 years. 54 (81.8%) had a bachelor degree in education. 48 (72.7%) of etiology were unspecified. 63 (95.5%) had partial or focal seizures. 58 (87.9%) of seizure frequency had no seizure or had it once in the last 3 months. All participants did not have adverse effects from antiepileptic medications. All records had compliance rates with the EQMs standard of more than 60% up to 100%. The overall mean score of QOLIE-31-P in the participants at 12-week follow-up was at a relatively moderate level and the energy subscale was lowest, while the daily activities subscale was highest. The Mood, Energy subscales and final QOL scores of patients with epilepsy had statistically significant differences between baseline and 12-week follow-up (p < 0.01). The seizure frequency indicated no significant differences between baseline and 12-week follow-up (p < 0.05). CONCLUSION: Researchers suggested that the QOLIE-31-P questionnaire for screening should become a routine practice for QOL assessment in PWEs and detection for signs of psychiatric symptoms that worsen QOL. Seizure frequency may not be the only single factor that represents a complete valid index to evaluate clinical outcomes. The EQMs standard may be applied to practice as it can resolve the missing necessary clinical data or gaps in care that may be beneficial to improve PWE patient care outcomes.